Influence of Thermal Treatment on the Adsorption Ability of Amorphous Alloys - O.M. Hertsyk; M.O. Kovbuz; L.M. Bednars'ka; B.Ya. Kotur (Adsorption Science & Technology)
The change in the adsorption abilities of surfaces of amorphous metallic alloys (AMA) after thermal treatment (at 77–773 K) was estimated by various physicochemical methods. It was shown that the extent of piperidine adsorption on an AMA surface subjected to thermal treatment correlated with the results of X-ray structural analysis.